SURGICAL REMOVAL OF A FIBROADENOMA IN A DOMESTICATED RAT (RATTUS NORVEGICUS): ORIGINAL CASE STUDY - I. H. Kathio; A. N. Tunio (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2016)
Fibroadenoma is a benign tumor composed of fibrous and glandular tissue. Mostly female rats have been victim of Fibroadenoma resulting from uterine abnormities. Mammary fibroadenoma tumor occurs due to estrogen and prolactin hormone imbalance. Such types of tumors have been observed in older women. We report a clinical case of 3-years old female brown rat, showed soft mass on left lateral thorax region. Rat tumor surgery was performed under injectable anesthesia using Xylazine at 0.1 mg/kg and Ketamine 100 mg/kg plus Acepromazine 0.01 mg/kg body weight administered intramuscularly. CO2 Laser (Luxar; model) was used to remove the tumor and wound was closed with Nylon 4-0 and skin staplers. It is concluded that histopathological findings of rat mass reported here confirm that adult rat has mammary fibroadenoma which is known as benign tumor.